The short- and long-run effects of fiscal consolidation in dynamic general equilibrium - Maik Wolters; Tim Schwarzmüller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We provide a systematic analysis of fiscal consolidation in a dynamic general equilibrium model with a detailed government sector and a share of credit-constrained households. We simulate permanent cuts in government consumption, government investment, and transfer payments as well as permanent increases in the labor, capital and consumption tax rate. We find that ordering these consolidation strategies by multiplier size or their welfare consequences leads to very different rankings. With respect to welfare gains cuts in government consumption rank highest because they yield the largest increase in private consumption in the short- and long-run. This however comes at the cost of large temporary reductions in output. Cutting transfers has the largest positive effects on output, yet the welfare consequences rank lowest since labor input does not decrease so that there is no increase in leisure. Cuts in government investment and capital tax increases have detrimental effects on output in the short- and long-run. From a welfare perspective they do not rank lowest because the slow convergence of the system to the final steady state leads to substantial discounting of the implied long-run drop in consumption. To explain these different outcomes we analyze the short- and long-run transmission channels of the different consolidation instruments. Furthermore, we study how the transmission of fiscal consolidation changes in the case of a binding zero lower bound on nominal interest rates.
Keywords: E62; E63; H61; 330